Chemical composition, antimicrobial properties, and antioxidant activity of galangal rhizome - ALJOBAIR,Moneera Othman (2022)
Abstract This study investigated the chemical composition (proximate composition, fatty acids, minerals, and phenolic compounds), antioxidant activity, and antimicrobial activity of galangal rhizomes. The rhizomes contain appreciable amounts of ash (5.38%), protein (5.86%), carbohydrate (81.13%), potassium (159.79 mg/kg), calcium (25.7 mg/kg), phosphorous (17.36 mg/kg), magnesium (15.57 mg/kg), iron (7.2 mg/kg) and manganese (3.82 mg/kg). Galangal rhizome oil is rich in unsaturated fatty acids (91.8%), elaidic (67.82%), linoleic (22.56%), palmitic (5.18%), and stearic (2.26%) acids found as the main fatty acids in the oil. Galangal rhizome extract contains substantial amounts of total phenolic content (53.18 mg GAE/g), total flavonoid content (14.12 mg CE/g), gallic acid (160.04 mg/100 g), (+)-catechin (124.33 mg/100 g), quercetin (105.34 mg/100 g), catechol (100.18 mg/100 g), isorhamnetin (82.2 mg/100 g), trans-cinnamic acid (81.97 mg/100 g) and protocatechuic acid (71.46 mg/100 g). The extract of galangal rhizomes also possessed high antioxidant activity, as assessed by DPPH (77.76%), ABTS (8.66 mmol TE/g), and FRAP (3.99 mmol TE/g), as well as antimicrobial activity against ten Gram-positive and Gram-negative pathogenic bacteria. In conclusion, Galangal is a rich source of nutrients and phytochemicals and exhibits antioxidant and antimicrobial activities.